INTERNAL AUDIT IN THE MANAGEMENT SYSTEM OF AN EDUCATIONAL INSTITUTION - A. Kagiyan; A. Ter-Grigoryants (Вестник Северо-Кавказского федерального университета, 2022)
The article is about questions of relationship between audit and consulting, the essence and methods of regulating the quality of audit in various countries, the stages of its development in the Russian Federation. Discusses the prerequisites for creating an internal audit service in educational institutions and suggested ways to improve the internal audit service. The relevance of the chosen topic is the rather complex structure of educational institutions and the availability of various sources offunding. These conditions require the functioning internal audit service. This will help to efficiently allocate and use available funds and eliminate risks.